(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
This paper focuses generally on educating tremendous writing capabilities to the English language learners. First of all, it discusses the importance of English asan worldwide language. Later, this paper lays emphasis on the significance of language abilities that are wanted for the ELLs to increase their conversation capabilities in English. Furthermore, it ordinarily focuses on the significance of the writing competencies of the English language. Then discloses the benefits of writing abilities for the ELLs. After that, it absolutely discusses the fantastic teaching of writing capabilities for the ELLs. Finally, this work also gives some valuable recommendations to both the teachers of English and the ELLs to increase their instructing and mastering writing skills.